Efeito do gás ozônico e do óleo de girassol ozonizado no crescimento in vitro do Pythium insidiosum canino - Carrijo, Bruna Nonato (2021)
Pythiosis is an infectious granulomatous disease caused by the aquatic oomycete Pythium insidiosum. Conventional treatments have reduced effectiveness against the chronic infection, which can be responsible for local and systemic damage in several species. In this context, ozone (O3) has shown high antimicrobial action against several pathogens, such as fungi and bacteria. Threfore, the present study aimed to characterize the effect of O3 gas and ozonated sunflower oil on the in vitro growth of P. insidiosum isolated from dogs. In Experiment 1, the pathogen was exposed to the O2-O3 gas mixture for different periods (72 μg O3 mL-1 for 5, 15 or 30 minutes) or with different concentrations (32, 52 or 72 μgO3 mL-1 for 30 minutes). In Experiment 2, fragments of P. insidiosum were covered with ozonized sunflower oils with different peroxide index (≤25, between 400 and 500 or ≥600 mmol-equiv. Kg-1 ). The growth area of the pathogen was digitally measured during the first 14 days’ post-treatment. Samples with absence of grow were recultured to assess the germicidal or germiostatic action of the respective treatment. In Experiment 1, exposure of P. insidiosum to O3 gas for 30 minutes showed germicidal action regardless of the concentration. However, samples of the pathogen exposed to O3 gas for 15 or 05 min showed similar growth rate when compared to the control group (P> 0.1). In Experiment 2, ozonized sunflower oil with a peroxide index ≥600 mmolequiv. kg-1 inhibit the growth of the pathogen. Considering the experimental conditions of the present study, the treatment with O2-O3 gas mixture for 30 minutes or sunflower oil with a high peroxide index have a germicidal action against P. insidiosum isolated from dogs. KEY WORDS: Dog; germicide; ozone therapy; peroxide; pythiosis.